2016
DOI: 10.1007/s12298-016-0336-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation assessment of acid lime accessions collected from south of Iran using SSR and ISSR molecular markers

Abstract: Iran has a long history of acid lime cultivation and propagation. In this study, genetic variation in 28 acid lime accessions from five regions of south of Iran, and their relatedness with other 19 citrus cultivars were analyzed using Simple Sequence Repeat (SSR) and Inter-Simple Sequence Repeat (ISSR) molecular markers. Nine primers for SSR and nine ISSR primers were used for allele scoring. In total, 49 SSR and 131 ISSR polymorphic alleles were detected. Cluster analysis of SSR and ISSR data showed that most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…'Siavaraz' is a local cultivar of sweet orange with a long history of cultivation in northern part of Iran, Mazandaran and Guilan provinces (Sharafi et al, 2016). It is a highly seedy and juicy cultivar with unknown origin (Sharafi et al, 2016). In the present study with a slight divergence this cultivar was found very closely related to Frost Valencia' and 'Washington Navel.…”
Section: Issr Polymorphism and Genetic Relationshipssupporting
confidence: 45%
See 3 more Smart Citations
“…'Siavaraz' is a local cultivar of sweet orange with a long history of cultivation in northern part of Iran, Mazandaran and Guilan provinces (Sharafi et al, 2016). It is a highly seedy and juicy cultivar with unknown origin (Sharafi et al, 2016). In the present study with a slight divergence this cultivar was found very closely related to Frost Valencia' and 'Washington Navel.…”
Section: Issr Polymorphism and Genetic Relationshipssupporting
confidence: 45%
“…The similarity value between them was 0.77. 'Siavaraz' is a local cultivar of sweet orange with a long history of cultivation in northern part of Iran, Mazandaran and Guilan provinces (Sharafi et al, 2016). It is a highly seedy and juicy cultivar with unknown origin (Sharafi et al, 2016).…”
Section: Issr Polymorphism and Genetic Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…To elucidate the precise traits of each accession, investigations of morphological traits and DNA analysis have been very effective (Ueda and Higuchi, 2012). New findings regarding several local citrus genetic resources were also reported using both morphological and molecular markers (Nasir et al, 2017;Sharafi et al, 2016;Tshering Penjor et al, 2014a, b).…”
Section: Introductionmentioning
confidence: 91%